العملات المشفرة كأداة لتسعير المنتجات الدولية: الفرص والتحديات - حميتي، نور الهدى (University Of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى استكشاف مدى إمكانية استخدام العملات المشفرة كأداة لتسعير المنتجات الدولية، متمحورة حول الفرص المتاحة والتحديات المحتملة. وتم اتباع المنهج الوصفي التحليلي. توصلت دراستنا إلى أن فرصة ناجحة التسعير المنتجات بالعملات المشفرة في التجارة الدولية يتوقف على عدة عوامل، وبشكل أساسي سيكون تطوير أطر تنظيمية قوية ومنسقة أمرا بالغ الأهمية للتخفيف من المخاطر وتعزيز بيئة آمنة لمعاملات التشفير، وأن التعاون العالمي يكتسي أهمية حاسمة حيث يجب على الهيئات الدولية والحكومات وصناعة التشفير العمل معا لتشكيل مشهد تنظيمي قابل للتكيف ومرن وشامل لتشجيع التبني والاستخدام المسؤول للعملات المشفرة. Abstract: This study aims to explore the extent to which cryptocurrencies can be used as a tool for pricing international products, centered on opportunities and potential challenges. The descriptive and analytical approach was followed. Our study found that the opportunity for successful pricing of products in cryptocurrencies in international trade depends on several factors, and fundamentally the development of strong and harmonized regulatory frameworks will be critical to mitigate risks and promote a secure environment for crypto transactions, and that global cooperation is crucial as international bodies, governments and the crypto industry must work together to form an adaptable, flexible and inclusive regulatory landscape to encourage the adoption and responsible use of cryptocurrencies.
مداخلة
Keywords: العملة المشفرة; التسعير; التجارة الدولية; المنتجات; Cryptocurrency; pricing; international trade; products